The Influence of Total Production, Labor Absorption, Market Access, and Business Capital on Increasing Local Community Income in the Cassava Cracker Industry in Brang Pelat Hamlet, Pelat Village - Erina Ade Saufitri; Edi Irawan (Takaza Innovatix Labs Ltd., 2026)
Locally-based micro, small, and medium enterprises (MSMEs) play a strategic role in improving the welfare of rural communities. The cassava cracker industry in Brang Pelat Hamlet, Pelat Village, is a growing MSME, but still faces various production and income limitations. This study aims to analyze the influence of total production, labor absorption, market access, and business capital on increasing local community income. The study used a quantitative approach with a causality design. Data were collected through questionnaires from 38 respondents from the cassava cracker industry selected by purposive sampling. Data analysis was conducted using classical assumption tests, multiple linear regression, and partial and simultaneous hypothesis tests. The results showed that total production, labor absorption, and business capital had a positive and significant effect on increasing community income, while market access did not have a significant effect partially. However, simultaneously, these four variables had a significant effect on increasing local community income. The conclusion of this study confirms that optimizing production, labor, and capital are key factors in increasing community income in the cassava cracker industry in rural areas.